2002
DOI: 10.1071/ch01194
|View full text |Cite
|
Sign up to set email alerts
|

Rhodomyrtone, an antibotic from Rhodomyrtus tomentosa

Abstract: The ethyl acetate extract of the leaves of Rhodomyrtus tomentosa (Ait.) Hassk. yielded rhodomyrtone (5) [6,8-dihydroxy-2,2,4,4-tetramethyl-7-(3-methyl-1-oxobutyl)-9-(2-methylpropyl)-4,9-dihydro-1H-xanthene-1,3(2H)-di-one] which had significant activity against Escherichia coli and Staphylococcus aureus. The structural elucidation followed from spectroscopic evidence and from a single-crystal X-ray structural determination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…Two compounds (1 and 2) were isolated from the 90% acetonitrile layer of peel, and two (3 and 4) from the seeds. Compound 2 was characterized as an acylphloroglucinol isolated from Rhodomyrtus tomentosa, 12) as previously reported. Compound 3 was identified as an acylphloroglucinol, isomyrtucommulone B. Appendino et al reported that isomyrtucommulone B is an isomer of myrtucommulone B, and was a thermal degradation product of a trimeric acylphloroglucinol, myrtucommulone A.…”
Section: Resultsmentioning
confidence: 91%
“…Two compounds (1 and 2) were isolated from the 90% acetonitrile layer of peel, and two (3 and 4) from the seeds. Compound 2 was characterized as an acylphloroglucinol isolated from Rhodomyrtus tomentosa, 12) as previously reported. Compound 3 was identified as an acylphloroglucinol, isomyrtucommulone B. Appendino et al reported that isomyrtucommulone B is an isomer of myrtucommulone B, and was a thermal degradation product of a trimeric acylphloroglucinol, myrtucommulone A.…”
Section: Resultsmentioning
confidence: 91%
“…4 H ‐Chromenes are a core structural feature of an array of fascinating natural products that have intriguing biological activities (Scheme ). For example, rhodomyrtone and rhodomyrtosone B show potent antibiotic activities,7 whereas the dimeric 4 H ‐chromene acylphloroglucinol, myrtucommulone E, serves as a promising α‐glucosidase inhibitor with antibacterial activity 8. These frameworks have become attractive targets in organic synthesis,9, 10 and, despite significant advances having been made, asymmetric methods for their construction are still extremely rare 11…”
Section: Methodsmentioning
confidence: 99%
“…During the past few years, a number of unusual phloroglucinol derivatives such as rhodomyrtone, 3 rhodomyrtosones, 4 and tomentosones, 5 have been isolated from Rhodomyrtus tomentosa. Among them, rhodomyrtone displayed potent anti-bacterial activity, especially against methicillin-resistant Staphylococcus aureus.…”
mentioning
confidence: 99%